Academic apartheid : race and the criminalization of failure in an American suburb - Drake, Sean J. (University of California Press, 2022)
"In Academic Apartheid, sociologist Sean J. Drake addresses long-standing problems of educational inequality from a nuanced perspective, looking at how race and class intersect to affect modern school segregation. Drawing on over two years of ethnographic observation and dozens of interviews at two distinct high schools in a racially diverse Southern California suburb, Drake unveils hidden institutional mechanisms that lead to the overt segregation and symbolic criminalization of Black, Latino, and lower-income students who struggle academically. His work illuminates how institutional definitions of success contribute to school segregation, how institutional actors leverage those definitions to justify inequality, and the ways in which local immigrant groups use their ethnic resources to succeed. Academic Apartheid represents a new way forward for scholars whose work sits at the intersection of education, race and ethnicity, class, and immigration"--